Analysis of the Cases of Covid-19 and Environmental Health for 14 Municipalities of the UGRHIs Baixo Pardo/Grande and Pardo - Rezende, Danilo; Alvares, Maria Eugênia Gonçalez; Ventura, Katia Sakihama (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Safety protocols emerged to minimize the spread of Covid-19 and are in force 20 months after the disease exists in Brazil. The occurrence of SARS-CoV2 can be analyzed by the local Environmental Health Indicator (ISA). The objective of this study was to analyze the mortality rate caused by Covid-19 about environmental and sanitary conditions in 14 municipalities in the state of São Paulo, located in the Baixo Pardo/Grande and Pardo UGRHIs. Data from covid-19 (total cases and deaths) were obtained by SEADE (2021) and research by Rezende (2021) and Alvares (2021) provided the ISA parameters. The municipalities were grouped by demographic density and those with up to 50 thousand inhabitants were selected. The fatality rate was obtained as the ratio of the number of deaths to the accumulated cases of Covid-19. Of the 14 selected municipalities, 57,1% met the research hypothesis (municipalities with higher ISA have a mortality rate at covid-19 below the national average) and seven of them are below 20 thousand inhabitants with mortality rates below 2,4 %. Studies based on data from Covid-19, socio-environmental parameters (schooling, income, age group) and social vulnerability conditions can contribute to a better interpretation of environmental health in the pandemic.